The deoxygenation mechanism of biomass thermal conversion with molten salts: Experimental and theoretical analysis - Dong, Lu; Liu, Yuhao; Wen, Huaizhou; Zou, Chan; Dai, Qiqi; Zhang, Haojie; Xu, Lejin; Hu, Hongyun; Yao, Hong (Renewable energy, 2023)
Utilizing molten salt for biomass pyrolysis has emerged as a pivotal technology for enhancing product value and has become a crucial alternative to traditional pyrolysis methods. However, there remains a dearth of research on the deoxygenation mechanism of biomass during molten salt thermal treatment. This study focuses on investigating the deoxygenation characteristics of biomass during molten salts thermal treatment through a comprehensive analysis involving experimental and density functional theory (DFT) study. Our experimental results revealed that, compared to traditional pyrolysis, molten salt (NaNO₃–NaNO₂) significantly increased oxygenated gas products, favoring deoxygenation during biomass conversion. Formic acid was employed as a simplified oxygen-containing model compound to investigate the decomposition characteristics with and without the presence of molten salts using DFT calculations. DFT studies of formic acid decomposition revealed lower activation energies on NaNO₃ (234.39 kJ/mol) and NaNO₂ (84.11 kJ/mol) surfaces compared to homogeneous reactions (234.63 kJ/mol). This indicates that NaNO₂ has a more pronounced promotional effect, facilitating formic acid decomposition. Furthermore, kinetic calculations show that both homogeneous and heterogeneous reaction rate constants for formic acid decomposition increase with temperature. The reaction rate constants on the surface of NaNO₃ are similar to homogeneous reactions, while it is much higher two on NaNO₂ surfaces. These findings highlight the critical role of NaNO₂ in formic acid decomposition within the NaNO₃–NaNO₂ molten salt system. The experimental and computational results elucidate the deoxygenation mechanism of biomass thermal conversion using molten salts and establish a theoretical foundation for the high-value utilization of pyrolysis products.